Measurement of Magnetic Island Width by Multi-Channel ECE Radiometer on HT-7 Tokamak - Han, Xiang; Ling, Bili; Gao, Xiang; Liu, Yong; Ti, Ang; Li, Erzhong; Xu, Liqing; Wang, Yumin (Plasma science & technology, 2013)
A 16-channel electron cyclotron emission （ECE） radiometer has been employed to observe the （m, n） = （2, 1） magnetic island structure on HT-7 tokamak, where m and n represent the poloidal and toroidal mode number respectively. The results indicate that the island width is about 7 cm when the magnetic island is saturated during the m/n = 2/1 mode. The location of resonance surface can be determined by plotting the contour of ECE relative fluctuation. This method could be applied to the HT-7 and EAST campaigns in the future for the research of neoclassical tearing modes （NTMs）.